Competition, Stability and Financial Crisis in Thai Banking Sector - PISEDTASALASAI, Anirut; RUJIRATPICHATHORN, Karnsiree (Journal of Advanced Studies in Finance; Vol 8 No 1 (2017): JASF Volume VIII Issue 1(15) Summer 2017, 2017)
This paper studies the trend of competition in banking industry in Thailand from 1992 to 2013. Furthermore, we investigate whether the change in the competition environment has any impacts on the financial stability of the banking system. First, we find that the competition level was volatile in the 1990s but became much more stable over the last 7 years . Secondly, our result suggests that the degree of competition in banking industry destabilizes the financial system due to equity capital reduction, higher banks risk-taking behavior and banks probability of default . However, by taking the 1997 Asian financial crisis into account; an increasing competition level after 1998 produces less negative effect to insolvency risk compared with the before-crisis period and the impacts of competition on banks equity capital and risk-taking behavior have started disappearing since then due to developments in financial market which diminish the loan market shares and increase portfolio diversification as well as the financial reforms in following years after the severe financial crisis.